Strategi Peningkatan Brand Loyalty dan Customer Satisfaction Bisnis Yogurt di Indonesia (Studi Kasus: PT Yummy Food Utama) - Indana Saramita Rachman; Aida Vitayala S Hubeis; Suryani Sidik F Motik (School of Business, Bogor Agricultural University (SB-IPB), 2017)
The objectives of this study were to analyze the key success factors of the yogurt business and recommend strategies to increase brand loyalty and customer satisfaction at PT Yummy Food Utama. The method used in this research was descriptive analysis method with case study approach at PT Yummy Food Utama with descriptive analysis, PESTEL framework, and Porter’s five forces. The result of descriptive analysis shows that the key success factors of yogurt business at PT Yummy Food Utama in terms of the behavior of the importance of consuming yogurt, accessibility products, and acceptability of the products are understanding the benefits of consuming yogurt, brand loyalty and product quality while the result of PESTEL framework and Porter’s five forces shows the strategies that has to be done by PT Yummy Food Utama on brand loyalty and customer satisfaction are retaining and maintaining the quality of products, educating the public and delivering the benefits of the importance of consuming yogurt, increasing the popularity of the product through the promotion by using electronic media (television advertising), establishing communication with consumers, opening up a free hotline